The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnbeh.2019.00191
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of the Neural Activity Related to Behavioral Decision-Making as Revealed by Event-Related Potentials

Abstract: Objective: To study the time course of the electrocortical activity evoked by gains and losses in the Iowa Gambling Task (IGT), the brain sources of this electrical activity, and its association with behavioral parameters of task performance in order to achieve a better knowledge of decision-making processes.Method: Event-related potentials (ERPs) were obtained from a 64-channel EEG in 25 participants when performing the IGT. Brain source localization analyses of the ERP components were also assessed.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…In line with what has been observed with fMRI, 5 many ERP studies showed that hypersensitivity to a reward undermines a person's ability to develop an optimal strategy 15,19 . More precisely, in a previous study, we found that participants with a blunted P300 showed better performance in the IGT, 19 while another group showed a positive correlation among all ERPs in IGT performance, except for the P300 20 . In addition, the P300 is related to the ability to discriminate relevant stimuli 21 .…”
Section: Introductionsupporting
confidence: 90%
“…In line with what has been observed with fMRI, 5 many ERP studies showed that hypersensitivity to a reward undermines a person's ability to develop an optimal strategy 15,19 . More precisely, in a previous study, we found that participants with a blunted P300 showed better performance in the IGT, 19 while another group showed a positive correlation among all ERPs in IGT performance, except for the P300 20 . In addition, the P300 is related to the ability to discriminate relevant stimuli 21 .…”
Section: Introductionsupporting
confidence: 90%
“…However, its specific association with rejected trials is somewhat surprising, given that positivity within this time range is thought to be associated with rewarding outcomes ("Reward positivity"; Donaldson et al, 2016;Heydari & Holroyd, 2016). This "reward positivity" interpretation is not universally supported, as some authors have identified similar P2 sensitivity with gains versus losses (San Martín et al, 2013) or increased P2 sensitivity with losses (Martinez-Selva et al, 2019;Schuermann et al, 2012), although these latter findings are exceptional cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the changed amplitude of P300 induced by tDCS could not explain the improved decision-making performance. One study suggested that early negative wave, P200, feedback-related negativity, P300 and late positive potential were all elicited during IGT [ 43 ]. In future, we can explore the other ERP components to better understand the electrophysiology mechanism of the modulation effect in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ERP studies viewed P300 as a typical indicator to reflect rewarding processing in decision-making under uncertainty [ 42 ]. In a gambling task, trials with monetary losses elicited larger P300 amplitude than trials with monetary gains [ 43 ]. Moreover, it was found that P300 amplitudes seem to increase depending on the result of feedback, with strongest changes elicited by the losses [ 44 ].…”
Section: Introductionmentioning
confidence: 99%